Pengaruh Bauran Pemasaran dan Kualitas Pelayanan terhadap Kepuasan Konsumen melalui Keputusan Pembelian di PT. Bali Coklat Junglegold Bali - Putu Dea Aulia Putri; Ni Luh Prima Kemala Dewi (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
Increasingly tight business competition requires companies to implement optimal marketing and service strategies to increase consumer satisfaction, especially in the midst of increasingly competitive premium chocolate industry competition. This study aims to analyze the effect of marketing mix and service quality on consumer satisfaction, both directly and indirectly through purchasing decisions as intervening variables. The analysis method used is Structural Equation Modeling (SEM) and analyzed using the Smart PLS Program. The sample in this study amounted to 100 respondents who were consumers of PT Bali Coklat Junglegold Bali. The results of the study indicate that, 1) Marketing mix and service quality partially have a significant effect on purchasing decisions. 2) Marketing mix and service quality partially have a significant effect on consumer satisfaction. 3) Purchasing decisions have a significant effect on consumer satisfaction. 4) Marketing mix and service quality partially have a significant effect on consumer satisfaction through purchasing decisions as a mediating variable at PT Bali Coklat Junglegold Bali.